Nonvalvular atrial fibrillation patients anticoagulated with rivaroxaban compared with warfarin exhibit reduced circulating extracellular vesicles with attenuated pro‐inflammatory protein signatures. (16th July 2021) - Weiss, Luisa; Keaney, John; Szklanna, Paulina B.; Prendiville, Tadhg; Uhrig, Wido; Wynne, Kieran; Kelliher, Sarah; Ewins, Karl; Comer, Shane P.; Egan, Karl; O'Rourke, Ellen; Moran, Eric; et al.
Abstract: Background: Rivaroxaban, a direct oral factor Xa inhibitor, mediates anti‐inflammatory and cardiovascular‐protective effects besides its well‐established anticoagulant properties; however, these remain poorly characterized. Extracellular vesicles (EVs) are important circulating messengers regulating a myriad of biological and pathological processes and may be highly relevant to the pathophysiology of atrial fibrillation as they reflect alterations in platelet and endothelial biology. However, the effects of rivaroxaban on circulating pro‐inflammatory EVs remain unknown. Objectives: We hypothesized that rivaroxaban's anti‐inflammatory properties are reflected upon differential molecular profiles of circulating EVs. Methods: Differences in circulating EV profiles were assessed using a combination of single vesicle analysis by Nanoparticle Tracking Analysis and flow cytometry, and proteomics. Results: We demonstrate, for the first time, that rivaroxaban‐treated non‐valvular atrial fibrillation (NVAF) patients (n=8) exhibit attenuated inflammation compared with matched warfarin controls (n=15). Circulating EV profiles were fundamentally altered. Moreover, quantitative proteomic analysis of enriched plasma EVs from six pooled biological donors per treatment group revealed a profound decrease in highly pro‐inflammatory protein expression and complement factors, together with increased expression of negative regulators of inflammatory pathways. Crucially, a reduction in circulating levels of soluble P‐selectin was observed in rivaroxaban‐treated patients (compared with warfarin controls), which negatively correlated with the patient's time on treatment. Conclusion: Collectively, these data demonstrate that NVAF patients anticoagulated with rivaroxaban (compared with warfarin) exhibit both a reduced pro‐inflammatory state and evidence of reduced endothelial activation. These findings are of translational relevance toward characterizing the anti‐inflammatory and cardiovascular‐protective mechanisms associated with rivaroxaban therapy.